The satisfaction level perceived by Italians during the first phase of the Covid-19 pandemic phase - Vitale, Elsa; Lupo, Roberto; Artioli, Giovanna; De Vito, Maria Francesca; Calabrò, Antonino; Caldararo, Cosimo; Ercolani, Maurizio; Lezzi, Alessia; Carvello, Maicol; Conte, Luana; Carriero, Maria Chiara (Acta Biomedica Atenei Parmensis, 2022)
Aim of the work.  To survey the degree of satisfaction of the Italian population in reference to the health care provided throughout the national territory in the period of emergency COVID-19.Methods. Observational, cross sectional, multicenter study conducted during the first phase of the pandemic (May-June 2020) involving the national population (n=889) subjects, through an online survey.Results. 889 people participated in the study. Among the perceptions regarding the level of satisfaction with the care received during the first pandemic wave, significant differences were found in the level of satisfaction with the health care received in general (p=.049), the degree of satisfaction toward the health care to people admitted to the hospital (p=. 046), to the treatment received for the COVID-19 test (p=.002), to the difficulty of contacting the general practitioner (.032), to the treatment received by their own health care company (p=.006), to the treatment received by the toll-free number (p